Servant Leadership Berdasarkan Analisis Teks Roma 12:3-8 Kajian Pendidikan Agama Kristen - Giban, Dr. Yoel; Sugiarsi, Ester; Rahardjo, Santoso Tanto (EDULEAD: Journal of Christian Education and Leadership, 2025)
This research explores a biblical model of leadership based on a textual analysis of Romans 12:3-8. Using a qualitative approach and hermeneutic analysis, this study identifies the leadership principles conveyed by the Apostle Paul in his letter to the church in Rome. Romans 12:3-8 emphasizes the importance of humility, the function of the body of Christ as one unified entity, and the use of spiritual gifts given by God for the common good. The main finding of this study is that effective leadership in the Christian context must include humility, recognition of the diversity of gifts within the community, and a commitment to serve others with integrity and love. The leadership model derived from this analysis can be applied in various church and Christian organizational contexts, with the goal of building a harmonious and productive community. This research contributes to the Christian leadership literature by providing a framework based on relevant biblical principles that are practical for everyday life.